Hypertension crisis as the first symptom of renovascular hypertension in children - Lingling Xu; Hongjun Ba; Xiaoyun Jiang; Youzhen Qin (BMC, 2022)
Abstract Background Renovascular hypertension (RVH) is one of the main causes of hypertensive crisis (HTN-C). It is characterized by acute onset and severe disease, and early diagnosis and treatment are difficult. The objective was to describe the characteristics of RVH and factors associated with RVH leading to HTN-C in children. At present, there are few clinical studies on RVH in children with large cases in China. Methods This study retrospectively analyzed the clinical data of inpatient children with RVH. Patients were divided into non-hypertensive crisis (non-HTN-C) group, and HTN-C group according to the first symptoms and blood pressure. Further, HTN-C were classified as hypertensive urgency (HTN-U) or hypertensive emergency (HTN-E). Results Fifty-four pediatric cases (41 boys and 13 girls) were included. 83.3% of the RVH cases were ≥ 6 years old. Three cases were classified into the non-HTN-C group. Of the 51 HTN-C cases, 18 cases were grouped as HTN-U and 33 as HTN-E. The HTN-U group were mainly asymptomatic (50.0%, 9/18) while the HTN-E group mainly presented with neurological symptoms (72.7%, 24/33). The number of unknown etiology children was 32 (59.2%). The top three known etiologies were Takayasu's arteritis (50.0%, 11/22), congenital renal dysplasia (27.3%, 6/22) and fibromuscular dysplasia (13.6%, 3/22). As for the target organ damage of RVH, patients had a higher prevalence of left ventricular hypertrophy (71.4%, 35/49) and retinopathy (77.8%, 21/27). Conclusions Most RVH patients with HTN-C as the first symptoms, especially for males over 6 years old, should be assessed for RVH even if they were asymptomatic. Most asymptomatic patients with RVH already had target organ damage, and symptomatic patients even developed life-threatening complications. As preventive measures, routine monitoring of BP during children's physical examinations is advised.